Evaluation of the Economic Benefit of Earlier Systemic Lupus Erythematosus (SLE) Diagnosis Using a Multivariate Assay Panel (MAP). Issue 11 (12th October 2020) - Clarke, Ann E.; Weinstein, Arthur; Piscitello, Andrew; Heer, Avneet; Chandra, Tarun; Doshi, Shivang; Wegener, John; Goss, Thomas F.; Powell, Tami
Abstract : Objective: Diagnosis of systemic lupus erythematosus (SLE) made by standard diagnostic laboratory tests (SDLTs) has sensitivity and specificity of 83% and 76%, respectively. A multivariate assay panel (MAP) combining complement C4d activation products on erythrocytes and B cells with SDLTs yields a sensitivity and specificity of 80% and 86%, respectively, presumably enabling earlier SLE diagnosis at lower severity, with associated lower health care costs compared with SDLT diagnoses. We compared the payer budget impact of diagnosing SLE using MAP (incremental cost of $108) versus SDLTs. Methods: We modeled a health plan of 1 million enrollees. SLE diagnosis among suspected patients was 9.2%. The MAP arm assumed 80%/20% of patients were tested with MAP/SDLTs, versus 100% tested with SDLTs in the SDLT arm. Prediagnosis direct costs were estimated from claims data, and postdiagnosis costs were obtained from the literature. Based on improved MAP performance, the assumed hazard ratio for diagnosis rate compared with SDLTs was 1.74 (71%, 87%, 90%, and 91% of patients who develop SLE are diagnosed in years 1 to 4 compared with 53%, 75%, 84%, and 88% of patients diagnosed with SDLTs). Results: Total 4‐year pre‐ and postdiagnosis direct costs for patients with suspected SLE tested with MAP were $59 183 666 compared with $61 174 818 tested by SDLTs, with lower costs in the MAP arm due primarily to prediagnosis savings related to reduced hospital admissions. Conclusion: Incorporating MAP into SLE diagnosis results in estimated 4‐year direct cost savings of $1 991 152 ($0.04 per member per month). By facilitating earlier diagnosis of SLE, MAP may enhance patient outcomes.